CONFIGURING WINDOWS SERVER HYBRID ADVANCED SERVICES EXAM REF AZ-801 configure advanced Windows Server services for on-premises, hybrid, and cloud environments - Gill, Chris (PACKT PUBLISHING LIMITED, 2023)
Ace the AZ 801 exam and master advanced Windows Server and Infrastructure-as-a-Service workload administration with this comprehensive guide Purchase of the print or Kindle book includes a free PDF eBook Key Features Gain practical knowledge to conquer the AZ-801 certification and tackle real-world challenges Learn to secure Windows Server in on-premises and hybrid infrastructures Leverage hands-on examples to monitor and troubleshoot Windows Server environments Book Description Configuring Windows Server Hybrid Advanced Services Exam Ref AZ-801 helps you master various cloud and data center management concepts in detail, helping you grow your expertise in configuring and managing Windows Server in on-premises, hybrid, and cloud-based workloads. Throughout the book, you'll cover all the topics needed to pass the AZ-801 exam and use the skills you acquire to advance in your career. With this book, you'll learn how to secure your on-premises Windows Server resources and Azure IaaS workloads. First, you'll explore the potential vulnerabilities of your resources and learn how to fix or mitigate them. Next, you'll implement high availability Windows Server virtual machine workloads with Hyper-V Replica, Windows Server Failover Clustering, and Windows File Server. You'll implement disaster recovery and server migration of Windows Server in on-premises and hybrid environments. You'll also learn how to monitor and troubleshoot Windows Server environments. By the end of this book, you'll have gained the knowledge and skills required to ace the AZ-801 exam, and you'll have a handy, on-the-job desktop reference guide. What you will learn Understand the core exam objectives and successfully pass the AZ-801 exam Secure Windows Server for on-premises and hybrid infrastructures using security best practices Implement, manage, and monitor Windows Server high availability features successfully Configure and implement disaster recovery services using Hyper-V features, Azure Recovery Services, and Azure Site Recovery Explore how to migrate various servers, workloads, and tools from previous versions of Windows Server to 2022 Monitor and troubleshoot Windows Server environments in both on-premises and cloud workloads using Windows Server tools, Windows Admin Center, and Azure services Who this book is for This book is for Cloud and Datacenter Management administrators and engineers, Enterprise Architects, Microsoft 365 Administrators, Network Engineers, and anyone seeking to gain additional working knowledge with Windows Server operating systems and managing on-premises, hybrid and cloud workloads with administrative tools. To get started, you'll need to have a basic understanding of how to configure advanced Windows Server services utilizing existing on-premises technology in combination with hybrid and cloud technologies.